THE FUTURO - Pamela Voigt (Docomomo Journal, 2022)
The Futuro by Matti Suuronen reflects the confidence in the possibilities of plastics as a new building material of post-war times. A number of the 70 to 100 Futuros that were built worldwide still exist and, generally, they are now being preserved. A comparison of four restoration approaches of Futuro Houses, dating from 2007 to 2018, has given insights into the specific constructive features, modifications and the challenge of their complex materiality and innovative design. This explains the complexity of the conservation process.